An improved four-parameter conjugated bond-based peridynamic method for fiber-reinforced composites. (November 2022) - Che, Lu; Liu, Shuo; Liang, Jun; Fang, Guodong
Highlights: An improved lamina conjugated BB-PD model is established. The proposed model contains four independent material parameters. The model eliminates the limitation of Poisson's ratio and shear modulus. An energy-based damage model for lamina is established. Abstract: The classical bond-based peridynamic (BB-PD) theory has inherent limitations on material properties when dealing with composites. An improved lamina conjugated BB-PD model with four independent material parameters is established to study the fracture behavior of composite materials. The model defines four basic generalized PD bonds, including fiber bond, matrix bond, fiber-matrix conjugated bond pair and matrix-matrix conjugated bond pair. Using the equivalent relationship of elastic strain energy density, the analytical expressions of the four micro-modulus in the improved lamina conjugated BB-PD model are determined. These four micro-modulus parameters can describe the four independent engineering material constants of the lamina, which eliminates the restriction of Poisson's ratio and shear elastic modulus for the composite materials. Moreover, an energy-based failure criterion is further proposed for the failure analysis of composite materials. In order to verify the capability and applicability of the proposed model, the displacement field and fracture behavior of the composite lamina with uniaxial tensile are simulated. In addition, the failure modes and crack propagation path of the laminae with different fiber orientations and initial crack angles are investigated by using the proposed model.